VARIASI JUMLAH KROMOSOM TALAS BENTUL (COLOCASIA ESCULENTA (L.) SCHOTT) IN VITRO HASIL PERLAKUAN ORIZALIN - Ermayanti, Tri Muji; Rantau, Deritha Ellfy; Wulansari, Aida; Martin, Andri Fadillah; Hafiizh, Erwin Al (JURNAL BIOLOGI INDONESIA, 2019)
ABSTRACTChromosome number analysis is required after polyploid induction with oryzalin. Flowcytometry analysis is a simple and quick method to determine the ploidy level, however, chromosome number analysis is needed in order to confirm variation in the chromosome numbers which has occurred. The aim of the research was to investigate chromosome number variation of polyploid taro (Colocasia esculenta) after in vitro treatment with oryzalin. Nine treated-oryzalin clones and four taro cultivars, as control treatment, were used in this experiment. Ploidy level confirmation was done by flowcytometry analysis, meanwhile chromosome number calculation was performed by squashing method. Roots were isolated from  in vitro plantlets for squashing, leaves were isolated from the same plantlets were used for flowcytometry analysis. At least three plants consisted of 6-52 cells having good chromosome distributions were calculated for their chromosome numbers. The results showed that ploidy level of taro corresponded to the number of chromosomes. Flowcytometry analysis of diploid, triploid, tetraploid as well as hexaploid clones, all has chromosome numbers similar to those as their ploidy levels. Range of the chromosome numbers varied, with most of cells had around their normal chromosome numbers. From 5 to 15% of cells had aneuploid numbers lower or above their normal chromosome numbers.  Keywords : Colocasia esculenta, flowcytometer, polyploid, chromosome number, oryzalin, in vitro